Dendritic spinule-mediated structural synaptic plasticity: Implications for development, aging, and psychiatric disease - Zaccard, Colleen R.; Gippo, Isabel; Song, Amy; Geula, Changiz; Penzes, Peter (Frontiers in Molecular Neuroscience, 2023)
Dendritic spines are highly dynamic and changes in their density, size, and shape underlie structural synaptic plasticity in cognition and memory. Fine membranous protrusions of spines, termed dendritic spinules, can contact neighboring neurons or glial cells and are positively regulated by neuronal activity. Spinules are thinner than filopodia, variable in length, and often emerge from large mushroom spines. Due to their nanoscale, spinules have frequently been overlooked in diffraction-limited microscopy datasets. Until recently, our knowledge of spinules has been interpreted largely from single snapshots in time captured by electron microscopy. We summarize herein the current knowledge about the molecular mechanisms of spinule formation. Additionally, we discuss possible spinule functions in structural synaptic plasticity in the context of development, adulthood, aging, and psychiatric disorders. The literature collectively implicates spinules as a mode of structural synaptic plasticity and suggests the existence of morphologically and functionally distinct spinule subsets. A recent time-lapse, enhanced resolution imaging study demonstrated that the majority of spinules are small, short-lived, and dynamic, potentially exploring their environment or mediating retrograde signaling and membrane remodeling via trans-endocytosis. A subset of activity-enhanced, elongated, long-lived spinules is associated with complex PSDs, and preferentially contacts adjacent axonal boutons not presynaptic to the spine head. Hence, long-lived spinules can form secondary synapses with the potential to alter synaptic connectivity. Published studies further suggest that decreased spinules are associated with impaired synaptic plasticity and intellectual disability, while increased spinules are linked to hyperexcitability and neurodegenerative diseases. In summary, the literature indicates that spinules mediate structural synaptic plasticity and perturbations in spinules can contribute to synaptic dysfunction and psychiatric disease. Additional studies would be beneficial to further delineate the molecular mechanisms of spinule formation and determine the exact role of spinules in development, adulthood, aging, and psychiatric disorders.